2010
DOI: 10.1007/s10682-010-9365-6
|View full text |Cite
|
Sign up to set email alerts
|

Natural selection on cork oak: allele frequency reveals divergent selection in cork oak populations along a temperature cline

Abstract: A recent study of population divergence at neutral markers and adaptive traits in cork oak has observed an association between genetic distances at locus <2/>ZAG46 and genetic distances for leaf size and growth. In that study it was proposed that certain loci could be linked to genes encoding for adaptive traits in cork oak and, thus, could be used in adaptation studies. In order to investígate this hypothesis, here we (1) looked for associations between molecular markers and a set of adaptive traits in cork o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 55 publications
(58 reference statements)
1
9
0
Order By: Relevance
“…This would be the case in our study for the potential outlier loci, which without being adaptive markers, could be used for the identification of selection effects. Similar selection effects have been reported in genetic studies of different oak species by using nuclear microsatellites (Neophytou et al, 2010;Ramirez-Valiente et al, 2010;Zhang et al, 2006). Further, large changes in allele frequencies at eight microsatellite loci observed in Drosophila populations indicated selectively-driven changes and provided evidence about genomewide selective sweeps that affect not only fitness but also linked neutral loci (Montgomery et al, 2010).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This would be the case in our study for the potential outlier loci, which without being adaptive markers, could be used for the identification of selection effects. Similar selection effects have been reported in genetic studies of different oak species by using nuclear microsatellites (Neophytou et al, 2010;Ramirez-Valiente et al, 2010;Zhang et al, 2006). Further, large changes in allele frequencies at eight microsatellite loci observed in Drosophila populations indicated selectively-driven changes and provided evidence about genomewide selective sweeps that affect not only fitness but also linked neutral loci (Montgomery et al, 2010).…”
Section: Discussionsupporting
confidence: 75%
“…These results were confirmed in studies of several tree species by using molecular genetic (Ohsawa and Ide, 2008). In this context, allele frequency differences at microsatellite loci revealed divergent selection in cork oak populations along a temperature cline (Ramirez-Valiente et al, 2010). Given that elevation gradients present many different site conditions, the impact of environmental factors on genetic structures is not evident.…”
Section: Introductionmentioning
confidence: 62%
“…This locus may be in linkage disequilibrium with a region of the genome that is affected by some or all of the factors in the environmental distance matrix. Other studies in the genus Quercus have found significant associations between microsatellite markers and genes coding for traits under selection [ 82 , 93 ]. ZAG15 has been mapped to linkage group 9 near QTL’s for leaf shape [ 94 ] and bud burst [ 95 ], and a study in Q .…”
Section: Discussionmentioning
confidence: 99%
“…First, populations experiencing different climates could have evolved particular adaptations, and reduced gene flow may be reflecting selection against the establishment of nonlocal genotypes even when neutral microsatellite markers are not involved in these evolutionary processes (Aitken et al. 2008; Ramírez‐Valiente et al. 2009, 2010; Eckert et al.…”
Section: Discussionmentioning
confidence: 99%